Implementation of Lean Six Sigma for Airline Ground Handling Process - Şenvar, Özlem; AKBURAK, DİLEK (My University, 2018)
Lean six sigma methodology offers a broad range of assessments and implementation services to meet the demands and challenges organizations face in today’s global marketplace, where improved processes and unobstructed flow are essential elements for reducing costs and maintaining a competitive advantage. So that organizations can maximize profits and increase business value by providing knowledge and guidance on implementing continuous improvement, culture change, methodologies and tools. From this standpoint, the purpose of this study is to analyze and enhance improvements for the non-value adding processes in airline ground handling operations via lean six sigma methodology and utilization of the appropriate tools.
Keywords: Lean Six Sigma; Airline Ground Handling Operation; DMAIC; Service Industry